The Use of Ispring Suite-Based Student Worksheets in Indonesian Language Learning-Poetry Writing Skills - Noviafitri, Kartika Satya; Huda, Miftakhul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: this study is to describe the application of iSpring Suite-based Learner Worksheets (LKPD) and to describe the learning outcomes in Indonesian language subjects, specifically on poetry writing skill indicators using iSpring Suite-based LKPD. The research was conducted at SMA Muhammadiyah 3 with class XI IPA 1 as the subject. Methodology: The methodology used direct observation techniques for data collection, and the learning process was implemented using the POPBL (Project Oriented Problem Based Learning) model. The data were presented descriptively in a qualitative manner, while the data analysis used descriptive statistics to provide an overview of students’ poetry writing skills. Results: The results showed that students’ poetry writing skills in POPBL learning with iSpring Suite-based LKPD achieved the highest score of 84 and the lowest score of 72, with an average score of 77.9. Based on these data, it can be concluded that 100% of the students achieved poetry writing ability scores above the KKM. Applications/Originality/Value: this research is that iSpring Suite-based LKPD can be used as an alternative learning tool to improve students’ poetry writing skills effectively and can serve as a reference for teachers to implement innovative learning models that integrate digital media and project-based learning.